THE COMPARISON OF SLAB DEFLECTION BASED ON FIELD MEASUREMENT, MANUAL CALCULATION (LEVY METHOD) AND FINITE ELEMENT METHOD (PROGRAM SAP 2000) (Jurnal Teknologi (Sciences & Engineering), 2016)
Concrete slab is a structural system that uses beams as a support element slab. The placement of beams at the whole edges of slab, so that the load received by the slab can be transfer into beams. The slab will be deformed/deflection when the loads are given. The value of slab deflection is dependent on the placement of beam support at the edges. This research was conducted on the two boundary condition that is simple support at the two edges and rigid support at whole edges. Calculating the value of deflection based on the results of field measurements and then compared with Marcus Levy method and Finite element method (FEM). Based on the study, the numbers of mesh affected to the value of deflection. The results of deflection with Program SAP 2000 will be approached deflection by Method M. Levy for the mesh division with large numbers. The deflection of slab on the field measurement approached manual calculations and Program SAP2000 with a simple support at the surrounding the edges.Â  The comparison of deflection was obtained for the simple support based on manual calculations and field measurement has a difference of 0.3% - 1%. Where the value of deflection on the field measurement is smaller than the manual calculation.